(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article focuses on the essence of the “gustative” notion and its interpretation in literature tale culinary for children. So, it is noted that Literary-gustative trend in the modern history and criticism of the literature determined the basic content of the concept “gustative” and also formed a concept of the gustative images in literature. The gustative image considered as complete system of content-formal qualities and function which constitute a series of olfatic factors of both the individual products and cooked dishes as well as the processes of its consumption by many contemporary literary critics. This understanding of gustative image contributes not only to study it as an element of the text, but to include it with linguistic means, tropes and stylistic figures in general philological analysis of literary work, its interpretation, which is based on the famed approaches, methods, technologies, schemes of analysis.